Left Ventricular Flow Dynamics with the HeartMate3 Left Ventricular Assist Device: Effect of Inflow Cannula Position and Speed Modulation. Issue 12 (8th July 2021) - Ortiz, Sean; Vu, Vi; Montes, Ricardo; May-Newman, Karen
Abstract : Supplemental Digital Content is available in the text. Abstract : Improper left ventricular assist device (LVAD) inflow cannula (IC) positioning creates areas of stasis and low pulsatility that predispose thromboembolism, but may be mitigated with LVAD speed modulation. A mock loop study was performed to assess the sensitivity of left ventricle (LV) flow architecture to IC position and speed modulation during HeartMate3 support. System pressure, flow, and the time-resolved velocity field were measured within a transparent silicone LV for three IC angles and three IC insertion depths at matched levels of cardiac function and LVAD speed. Inflow cannula angulation towards the septum increased the resistance to LVAD flow as well as increasing the size and energy of the counter-clockwise (CCW) vortex. Apical velocity was reduced compared to IC angulation towards the mitral valve, but regional pulsatility was maintained across all angles and LVAD speeds. Increased IC protrusion decreased LVAD flow resistance, increasing velocity within the IC but reducing flow and pulsatility in the adjacent apical region. Increasing LVAD flow resistance improves aortic valve opening and strengthens the CCW vortex which directs inflow towards the septum, producing higher blood residence time and shear activation potential. Despite this impact on flow architecture, pulsatility reduction with increased LVAD speed was minimal with the HeartMate3 speed modulation feature.